IN VITRO ANTAGONISM OF THE ISOLATE MUSHROOM Trichoderma harzianum TO Fusarium oxyzporum f. sp. Cubense CAUSES WILT DISEASE IN BANANA KEPOK (Musa paradisiaca normalis) - Pattikawa, Apriyanti Santi; Pagaya, Joseph; Patty, Jogeneis (Universitas Pattimura, 2020)
Trichorderma harzianum is a soil native fungus that is beneficial because it has high antagonistic properties against plant pathogenic fungi. Control mechanisms can be: antibiosis, parasitism, competition and hyphae interference. T. harzianum as a biological control agent for the pathogenic fungus Fusarium oxyforum f. sp. Cubense is an alternative to control this pathogenic fungus, without causing a negative impact on the environment. The aim of the study was to determine whether Trichodernma harzianum isolates Piru, Kairatu and Uraur could suppress the growth of the fungus Fusarium oxyforum f. sp. cubense and Trichorderma harzianum which isolates (Piru isolate, Kairatu isolate and Uraur isolate) had faster inhibition against Fusarium oxyforum f. sp. cubense causes wilt disease on banana kepok (Musa paradisiaca normalis) in vitro with antagonism test. The research was conducted in 2 places, namely in the HPT BPTPH laboratory in Maluku province and continued in the microbiology laboratory at FMIPA Unpatti. The research method used was laboratory experimental in nature by using a completely randomized design with factorial pattern with three treatments and three replications. The results showed that the cause of wilt disease in banana plants was Fusarium oxyforum f. sp. Cubense. Antagonism test in vitro showed that T. harzianum Piru isolate showed the highest inhibition zone (70.87%), both Kairatu isolates (45.27%), and the lowest by Uraur isolate (32.61%) so that it can be said that T. harzianum has the potential to inhibit the growth of Fusarium fungus. oxyforum f. sp. Cubense.